2023
DOI: 10.3233/adr-220062
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Network Connectivity and Cognitive Function Changes After Exercise Training in Older Adults with Intact Cognition and Mild Cognitive Impairment

Abstract: Background: Despite growing evidence regarding the association between exercise training (ET) and functional brain network connectivity, little is known about the effects of ET on large-scale within- and between-network functional connectivity (FC) of core brain networks. Objective: We investigated the effects of ET on within- and between-network functional connectivity of the default mode network (DMN), frontoparietal network (FPN), and salience network (SAL) in older adults with intact cognition (CN) and old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…These structural effects may facilitate functional network connectivity, as suggested by some reports linking better white matter structural connectivity to better functional connectivity within networks ( Neudorf et al, 2022 , Rieck et al, 2020 ). Additionally, exercise interventions in older cognitively normal adults and those with MCI have demonstrated exercise-related alterations in resting-state connectivity within the SAL and DMN ( Won et al, 2023 ) that are accompanied by exercise-related gray matter neurite density changes within the same networks. ( Callow et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These structural effects may facilitate functional network connectivity, as suggested by some reports linking better white matter structural connectivity to better functional connectivity within networks ( Neudorf et al, 2022 , Rieck et al, 2020 ). Additionally, exercise interventions in older cognitively normal adults and those with MCI have demonstrated exercise-related alterations in resting-state connectivity within the SAL and DMN ( Won et al, 2023 ) that are accompanied by exercise-related gray matter neurite density changes within the same networks. ( Callow et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this perspective, a few observational studies among older cognitively normal and non-demented individuals have reported links between greater levels of physical activity ( Soldan et al, 2022 , Soldan et al, 2021 ) or physical fitness ( Voss et al, 2016 ) with greater connectivity in the default-mode network and with greater network segregation. Similarly, exercise interventions among non-demented older adults have demonstrated exercise-related enhancements of within-network connectivity in functional networks ( Meng et al, 2022 , Menon, 2011 ), including the default mode, salience, and frontoparietal networks ( Dion et al, 2021 , Porto et al, 2018 , Won et al, 2021 , Won et al, 2023 ). Self-reported sleep quality has also been shown to have a positive association with default mode and attentional network connectivity in cognitively normal older adults, whereas subjective sleep disturbances and disorders in those with MCI are associated with reduced default mode connectivity ( Luo et al, 2022 , McKinnon et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Less walking was recognized by many participants as the reason for mobility decline over the pandemic. Walking interventions have been shown to improve mobility and cognition in older adults (Fanning et al, 2021; Won et al, 2023). Unique interventions that build on what is known about motivation and exercise are necessary to improve consistency with physical activity in the older adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they might reduce the risk of dementia by 40% (Livingston et al, 2020 ). There is rapidly growing evidence that physical activity or exercise can enhance neurocognitive functioning, widespread network connectivity, and white-matter integrity in both cognitively healthy older adults and those with cognitive decline (Konwar et al, 2023 ; Won et al, 2023 ). Santiago and Patashkin 's review specifically suggests that physical activity may be an effective treatment or preventative strategy for neurodegenerative diseases.…”
Section: Insights In Modifiable Factors In Neurocognitive Agingmentioning
confidence: 99%